The Unique Communication Pattern of Japanese and Indonesian Families Shaping Specific Character to their Children - Dwi Rini Sovia Firdaus; Alo Karyati; Rakhe S. Rakasiwi; Tubagus Nugraha (Institut Pertanian Bogor, 2022)
The character-building system in Japan has become a role model in Indonesia. The initiators of education policies in Indonesia are intensively promoting character building as a solution to the decline in the quality of human resources. Character building in Japan and in Indonesia are carried out by the nuclear family at home. This study maps the differences in the communication patterns of Indonesian and Japanese parents in teaching character building to their children. Parents of productive age 17-50 years were used as respondents, had junior high school to postgraduate education, and had children aged 0-15 years. Questionnaires were distributed using google forms to Japanese people in Japan and Indonesians in Indonesia. It was found that the value of hard work in Indonesian families stems from the desire to avoid uncertainty and parents’ pragmatic thinking. In Japanese families, avoiding uncertainty teaches children a spirit of enthusiasm. Hofstede's cultural dimensions cannot explain the source of the spirit of togetherness in Indonesian and Japanese families, as well as the source of the spirit of hard work, and responsibility in Japanese families.